Benchmarking as a quality of care improvement tool for patients with ST-elevation myocardial infarction: an NCDR ACTION Registry experience in Latin America. (12th December 2019) - Caixeta, Adriano; Franken, Marcelo; Katz, Marcelo; Lemos, Pedro A; Gomes, Ivanise; Yokota, Paula Ko; V Alliegro, PatrÍcia; Pesaro, Eduardo E; Neto, Miguel Cendoroglo; Valentine, C Michael; Brindis, Ralph G; Makdisse, Marcia
Abstract: Objective: We aim to examine the effect of benchmarking on quality-of-care metrics in patients presenting with ST-elevation myocardial infarction (STEMI) through the implementation of the American College of Cardiology (ACC) National Cardiovascular Data Registry (NCDR) ACTION Registry. Design: From January 2005 to December 2017, 712 patients underwent primary percutaneous coronary intervention PCI—499 before NCDR ACTION Registry implementation (prior to 2013) and 213 after implementation. Setting: STEMI. Participants: 712 patients. Intervention(s): Primary PCI. Main Outcome Measure(s): We examined hospital performance for the quality indicators in processes and outcomes of the management of patients presenting with STEMI. Outcome measures include door-to-balloon time (DBT), antiplatelet therapy and anti-ischemic drugs prescribed at discharge from pre-NCDR ACTION Registry to post-implementation. Results: There was improvement in DBT, decreasing from 94 min in 2012 (before NCDR adoption) to reach a median of 47 min in 2017 ( P trend  < 0.001). The percentage of cases with the optimal DBT of < 90 min increased from 55.8% before to 90.1% after the implementation of the NCDR ACTION Registry ( P trend  < 0.001). The rate of aspirin (90.3–100%, P  < 0.001), P2Y12 inhibitor (70.1–78.4%, P  = 0.02), beta-blocker (76.8–100%, P  < 0.001) and angiotensin-converting enzyme inhibitors or angiotensin receptor blockers (60.1–99.5%, P  < 0.001) prescribed at discharge increased from pre-NCDR ACTION Registry to post-implementation. Adjusted mortality before and after NCDR ACTION Registry implementation showed significant change (from 9.04 to 5.92%; P  = 0.027). Conclusions: The introduction of the ACC NCDR ACTION Registry led to incremental gains in the quality in STEMI management through the benchmarking of process of care and clinical outcomes, achieving reduced DBT, improving guideline-directed medication adherence and increasing patient safety, treatment efficacy and survival.